PENENTUAN KONSENTRASI AKTIVITAS URANIUM DARI INDUSTRI FOSFAT MENGGUNAKAN DETEKTOR ZnS(Ag) - Setiani, Indri; Munir, Mohammad; Firdausi, K. Sofjan; Bunawas, Bunawas (BERKALA FISIKA, 2006)
The activity concentration measurement of uranium (U238) in yellowcake sample which is coming from phosphate fertilizer industry P.T. PETRO KIMIA Gresik by using ZnS(Ag) detector has been done. In order to do this measurement, it is needed to callibrate and calculate the minimum detectable level of the detector. From the five samples that contain different yellowcake concentration, 400 mg of each samples were placed on five 2-inches-diameter stainless steel planchettes. HNO3 solution were added and the samples were shaken in order to make the samples as homogeneous as possible. The samples were totally evaporated under an infrared lamp until dry. Then they were counted by ZnS(Ag) detector. The uranium activity concentration measurement result of this method shows that sample with highest concentration of yellowcake (100%) have concentration activity 2,37 Bq/mg. While the sample with lowest concentration of yellowcake (37,5%) have concentration activity 0,95 Bq/mg. Key words : uranium, phosphate fertilizer industry, ZnS(Ag) detector, yellowcake